The Effect of Red Ginger Extract (Zingiber officinale var rubrum) on The Thickness of The Epitelial and Diameter of Seminiferous Tubules in Albino Rat (Rattus norvegicus) Exposed Monosodium Glutamat - Renaldi, Nogi; Rachmawati, Kadek; Widiyatno, Thomas Valentinus; Madyawati, Sri Pantja; Dhamayanti, Yeni (Universitas Airlangga, 2024)
Background: This study examined administration of MSG intraperitoneally to white rats resulted in a decrease in testicular weight, an increase in lipid peroxidase levels The testes, as the site of spermatogenesis, are highly vulnerable to oxidation processes caused by free radicals, which can disrupt spermatogenesis. Free radicals can be countered by antioxidants. One plant believed to have antioxidant activity is red ginger. Purpose: To determine the effect of red ginger against histopathology seminiferous tubules of white rat (Rattus norvegicus) exposed by monosodium glutamate. Methods: This study used 30 rats which were divided into 5 groups. The positve control group (K+) were given only monosodium glutamate 5g/kgBW and CMC Na orally, the treatments groups P1 were given monosodium glutamte 5g/KgBW + red ginger 50mg/rat/day, P2 were given 5g/KgBW + red ginger 100mg/rat/day, and P3 were given 5g/KgBW + red ginger 200mg/rat/day. All treatments were administered for 42 days. After 42 days of treatments, all rats were sacrificed and seminiferous tubules were observed with microscope from pathology laboratory. Results: Administration of red ginger extract can defend seminiferous tubules epithelial thicknes and diameter from exposure of monosodium glutamate with 100mg/KgBW dosage as the most effective dosage. Seminiferous tubules epitelial thickness and diameter were tested using one-way ANOVA and Duncan's multiple range test. Conclusion: Red Ginger Extract (Zingiber officinale var rubrum) has shown potential effects to counteract Monosodium Glutamat consequences on The Thickness of the epitelial and diameter of seminiferous tubules of white rat (Rattus norvegicus).